"Pengaruh PO (Penilaian Objektif) Pembimbing Dan PO (Penilaian Objektif) Penguji Terhadap Kualitas Kelulusan Mahasiswa Pada Perguruan Tinggi Raharja" - Ageng Setiani Rafika; Ki Ahmad Saputro; Riyan Nova Saputra (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2015)
Currently, many graduate students who can’t be absorbed by the world of work or labor market because of poor quality. It is caused by several factors such as students as learners, lecturer as a teacher, and the campus as a connector between the institution or any of its faculty and students to students and faculty facilities. The purpose of this study was to determine the effect of student discipline in implementing the guidance of the thesis as well as to determine the influence of PO coach and PO testers on the level of quality of graduation. This study uses a quantitative approach with descriptive correlational survey method. The sample collection technique is based on the calculation formula Slovin as many as 61 people. Data was collected using questionnaires and documentation. Analyzed using descriptive statistics and statistical analysis iferensial. Data processing using SPSS. Results of the study showed that the better the level of completion of Objective Assessment Supervisor, the better the quality level graduation because the value received will better the automatic IPK and also rose. However, the better the level of completion of Objective Assessment Examiners, will not affect the level of quality of the graduation.